Learning the Five Senses of Humans in Children aged 11-15 Years through Digital-Based Media in LubukPandan Village - Anisa Septiawan; Asep Bayu Dani Nandiyanto (Jurnal Nusantara Mengabdi, 2022)
Purpose: This study aims to share information, teach, and repeat learning about the five human senses to 23 children aged 11-15 years in Lubuk Pandan Village. Research Methods: This research method uses various digital-based media such as Google, WhatsApp and Youtube to collect and share information with children and uses Google Forms to provide pre-test and post-test in measuring the level of success in delivering material. Result: The results of both tests showed that most children experienced an increase in scores on the post-test, although there were some children who experienced a decrease in the post-test. This can be proven by the average score which has increased from 57.61 in the pre-test to 82.17 at the post-test. So these results show that digital media is able to improve children's literacy and understanding of the learning that has been delivered. Limitations: The limitation in this study is that it is difficult to be interactive between researchers and children due to various obstacles, one of which is due to the limited schedule of using cellphones by parents. Contribution: This research contributes to children to help them to know and learn and repeat the lessons of the five senses that have been learned in school.